Pengaruh Penerapan Model Direct Instruction Terhadap Persepsi Dan Hasil Belajar Psikomotor Siswa Dalam Pembelajaran IPA Fisika Di Kelas VIII SMPN 18 Pekanbaru - Berry Kurnia Vilmala (Faculty of Teacher Training and Education, 2019)
This study aims to determine the effect of the implementation of Direct Instruction model of perception and psychomotor learning outcomes in science learning physics class VIII student at SMP 18 Pekanbaru in the academic year 2011/2012 semester on the subject matter of light reflection. The research was conducted by the research design Postest-Only Control Design. The population in this study were all students in grade school N 18 Pekanbaru VIII and VIIIA-class research samples and VIIIG. The research instrument used was the study and data collection instrument. Data collection techniques are tests of psychomotor learning outcomes and the provision of a questionnaire administered after the learning process is completed. Data were analyzed through descriptive and inferential analysis. From the results of descriptive analysis of data obtained by the average absorption of psychomotor skills of physics students in science class and the class of experiments is very good control and effectiveness in the category of very effective learning.Exhaustiveness experimental class learning objectives stated otherwise completed while control classes are not complete. Of inferential analysis is performed based on hypothesis testing of learning outcomes of students psychomotor obtained tcount = 9.293 and = 1.688 TTable. In order to obtain student perceptions questionnaire t count = 6.055 and = 1.667 TTable. Psychomotor learning outcomes and student perceptions based on inferential test above the 95% confidence level.